Strongly Transitive Maps on Symmetric Products - Méndez, Héctor; Rito, Leonel (Topology Proceedings, 2022)
Let X be a compact metric space and let f: X → X be a continuous map. For a positive integer n, let F_n(X) be the hyperspace of all nonempty subsets of X with at most n points. Let f_n: F_n(X) → F_n(X) be the induced map defined by f_n(A)= f(A). In this paper, we study the connection between some d y namical properties of f and f_n. In particular, we are interested in the presence of the property of strong transitivity. Along the exposition, we study some aspects of the dynamics of gap subshifts.